A infância em disputa: escolarização e socialização na reforma de ensino primário em Minas Gerais 1927 - Cleide Maria Maciel de Melo (2010)
This study investigated the process of schooling in Minas Gerais state, in the late years of the First Republic (Primeira Republica). The First Elementary Instruction Congress (Primeiro Congresso de Instrução Primaria), which took place in Belo Horizonte from the 9th to the 18thof May, 1927, was used as the starting point for this work. The mentioned event, promoted by President Antonio Carlos de Andrada and the Secretary Francisco Campos government, aimed at supporting the elementary school reform, which would be decreed in October of thesame year. From the perspective of micro history, the records of three daily newspapers were analyzed Minas Geraes, Correio Mineiro and Diario de Minas along with Revista de Ensino (Teaching Magazine). We tried to bring to light the dynamics of the Congress, identify the congressmen/congresswomen who took part in the event, understand the representations of the schools and, especially, the way the schools dealt with childrens socialization in educational spaces such as school, family, work and the streets. This thesis sought to show that childhood was regarded as an object of dispute between representatives of three fields: political, medical and pedagogical, at that particular moment of education in Minas Gerais